Evaluasi Peraturan Bupati Nomor 47 Tahun 2022 tentang Program Keluarga Harapan Inklusif Kabupaten Gresik - Fintiyah, Apriliya; Radjikan; Muhammad Roisul Basyar (Public Sphere Review, 2026)
This study evaluates the implementation of Regent Regulation No. 47 of 2022 concerning the Inclusive Family Hope Program (PKH) in Gresik Regency through the dimensions of policy output and policy outcome using Ripley's (1985) evaluation framework. Using a descriptive evaluative qualitative approach, data were obtained through in-depth interviews with seven key informants, non-participant observation, and documentation study, and analyzed using the Miles and Huberman (1994) model. The results show mixed policy outcomes: high service accuracy and accountability through consistent distribution mechanisms, digital transparency, and multiple layers of control; sufficiently inclusive access with home visit innovations, although exclusion errors still exist; bias can be minimized but is still hampered by data inconsistencies; and program coverage and suitability are still limited due to budget constraints and the dilemma of recipient rotation. In terms of policy outcomes, short-term impacts are evident in increased public awareness, high rates of community reporting, and improved implementation capacity; medium-term impacts are seen in changes in community behavior and government responsiveness. However, the long-term impact still serves as a basic safety net for vulnerable groups. The main supporting factors are political commitment, cross-level coordination, and electronic data systems; while obstacles include budget constraints, unsynchronized data, insufficient monitoring, and inadequate assistance amounts. The study recommends expanding coverage through funding diversification, data synchronization, strengthened monitoring, evaluation of the rotation system and assistance amounts, and integration with empowerment programs. This study enriches the social policy evaluation literature and emphasizes the importance of sustainable program design for groups with permanent limitations.